A View of Time in Open and Distance Learning - Fang Jing, Hoo; Mohd Noh, Mohd Amin; Ibrahim, Raihan; Ilias, Mohd Faeez (SCAD Independent, 2022)
Time is a significant and massive worry in behaviour that causes difficulties amongst instructors and learners in ensuring an effective process of teaching and learning in open and distance learning (ODL) environment. This study aimed to identify instructors’ and learners’ ability to allocate time in ODL. The study was conducted with 320 respondents, and the instrument used was questionnaires. The results showed that ODL instructors and learners were challenged with many obstacles to prioritizing tasks and allocating time accordingly in their teaching and learning. A close inspection of the role of time management is much required. The most reported challenges were managing the academic schedule on ODL and multitasking while teaching and learning on ODL. Lastly, it was deemed unnecessary to have additional time to satisfy the expectations of ODL. It was found that both instructors and learners from public and private higher education institutions needed effective educational practices to succeed in ODL and blended learning. In short, time allocation in prioritizing tasks is still an obstruction to achieving effective and balanced teaching and learning system with ODL that satisfies the desire of the instructors and learners. This research suggests investigating social, cognitive, teaching and emotional presence to successfully conduct the teaching and learning process.